Wątki iberyjskie w astronomicznym traktacie Jana z Głogowa (1445–1507) - Zawadzki, Robert K. (Rzym a Półwysep Iberyjski: Różnorodność relacji od starożytności po współczesność, 2019)
The article offers an analysis of the reception of Iberian threads running through the astronomical treatise Introductorium compendiosum in Tractatum sphaerae materialis Ioannis de Sacrobusto of Jan of Głogów by applying a literary analysis of the research text. The author of the article hints at the paradoxical symbol of the Iberian countries, which were regarded both as being at the end of the world from the times of the Greeks and Romans as well as a base or starting point from which the great transatlantic voyages were begun to discover new lands and continents. The reader is also given an insight into the achievements of scholars such as Isidorus Hispalensis (the Bishop of Seville), Paulus Orosius and Averroes, who were descended from the Iberian peninsula and had an effect or influence on Jan’s dissertation.